Intersection of Effort and Risk: Ethological and Neurobiological Perspectives - Miller, Mike A.; Thome, Alexander; Cowen, Stephen L. (Frontiers in Neuroscience, 2013)
The physical effort required to seek out and extract a resource is an important consideration for a foraging animal. A second consideration is the variability or risk associated with resource delivery. An intriguing observation from ethological studies is that animals shift their preference from stable to variable food sources under conditions of increased physical effort or falling energetic reserves. Although theoretical models for this effect exist, no exploration into its biological basis has been pursued. Recent advances in understanding the neural basis of effort- and risk-guided decision making suggest that opportunities exist for determining how effort influences risk preference. In this review, we describe the intersection between the neural systems involved in effort- and risk-guided decision making and outline two mechanisms by which effort-induced changes in dopamine release may increase the preference for variable rewards.